The Wheel - Shackleton, Caroline; Turner, Nathan Paul (NewYork Cambridge University, 2014)
It looks simple, but nothing has changed the way we live more than the wheel. Could it be our greatest invention ?
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level; Invention